Preliminary suicide trends during the COVID-19 pandemic in Milan, Italy. (November 2021) - Calati, Raffaella; Gentile, Guendalina; Fornaro, Michele; Tambuzzi, Stefano; Zoja, Riccardo
Abstract: Europe was the second most affected continent by the 2019 coronavirus disease (COVID-19) pandemic, with Italy paying very high death tolls, especially in Lombardy, a region in Northern Italy. The pandemic profoundly impacted mental health and the world's rates of suicide since its outbreak. COVID-19-related suicide rates nonetheless followed a non-linear trend over the pandemic, decreasing after the COVID-19 outbreak, then raising during an extended follow-up period. Thus, we aimed to further assess the suicide rates in Lombardy. We carried out a retrospective analysis of all the autopsies performed in the year 2020 and within the first four months of the year 2021 through the database of the Institute of Forensic Medicine in Milan. In the year 2020, the recorded suicides decreased in comparison to 2016-2019 (21.19-22.97% of the autopsies), being 98 (18.08% out of 542 autopsies), while, in the first 4 months of the year 2021, 35 suicides were documented (185 autopsies, overall). Since the region of Lombardy was severely affected by COVID-19 since the early months of the year 2020, the extended retrospective follow-up allowed for firmer conclusions and insights about the need to extend the follow-up of COVID-19 pandemic beyond the first months after the outbreak, worldwide. This is with special emphasis towards the need to allocate the proper funds for mental health prevention for the general population as well as the most vulnerable ones, such as people with severe mental illness and caregivers, frontline health workers, and others bereaved by COVID-19.